2016
DOI: 10.1371/journal.pone.0146241
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Smoking during Pregnancy and Low Birthweight: Effects by Maternal Age

Abstract: BackgroundMaternal smoking during pregnancy has been consistently related to low birthweight. However, older mothers, who are already at risk of giving birth to low birthweight infants, might be even more susceptible to the effects of maternal smoking. Therefore, this study aimed to examine the modified association between maternal smoking and low birthweight by maternal age.MethodsData were obtained from a questionnaire survey of all mothers of children born between 2004 and 2010 in Okinawa, Japan who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…Other related risk factors are included pre-pregnancy weight, parity, history of prior LBW, gestational weight gain and caloric intake, general morbidity and illnesses, malaria, maternal HIV infection cigarette smoking, alcohol consumption, and history of LBW and prematurity [ 11 , 14 , 24 ]. For example, a study by Zheng et al among 92,641 mothers in Okinawa showed that maternal smoking was significantly associated with LBW in all age groups, while Coutinho et al found that smoking beyond the fourth month of pregnancy was a risk factor for LBW, irrespective of the number of cigarettes smoked per day [ 12 , 25 ]. Mother’s level of hemoglobin, and baby’s birth interval are also associated with LBW [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other related risk factors are included pre-pregnancy weight, parity, history of prior LBW, gestational weight gain and caloric intake, general morbidity and illnesses, malaria, maternal HIV infection cigarette smoking, alcohol consumption, and history of LBW and prematurity [ 11 , 14 , 24 ]. For example, a study by Zheng et al among 92,641 mothers in Okinawa showed that maternal smoking was significantly associated with LBW in all age groups, while Coutinho et al found that smoking beyond the fourth month of pregnancy was a risk factor for LBW, irrespective of the number of cigarettes smoked per day [ 12 , 25 ]. Mother’s level of hemoglobin, and baby’s birth interval are also associated with LBW [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second-hand tobacco smoke exposure and indoor air pollution remain two major health problems, especially in developing countries, and the effect of passive smoking and cooking smoke on neonatal birth weight has been debated. Smoking during pregnancy can increase the risk of preterm birth, fetal growth restriction, low birth weight, sudden infant death syndrome, and behavioral problems [ 3 , 4 , 5 , 6 ]. Although multiple substances have been identified in cigarette smoke, carbon monoxide (CO) and nicotine are the two responsible for adverse effects on the developing fetus [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The birth weight increase by 0.01 kg per one year increase in the age of the mother. This finding disagree with a 2016 fining [38]. This is due to the reason that the awareness of mothers will be increased as their age increases due to the repeated exposure which finally makes them to take enough quantity and quality of nutrient necessary for their fetus growth [6].…”
Section: Discussionmentioning
confidence: 84%